Integration of Islamic Values in the Education, Political, and Judicial Institutions in Indonesia - Mutiara Citra; Siti Halimah (Yayasan Pendidikan Islam (YPI) AN NUR INSANI, 2026)
The integration of Islamic values into Indonesian educational, political, and judicial institutions is a strategic effort to build a civilized and just social order. Islam, as areligion of rahmatan lil 'alamin (blessing for the universe), provides universal principles not only for the vertical relationship between humans and God but alsofor social and institutional interactions. In the realm of education, Islamic values contribute to the formation of character, morality, and spiritual competence. Inpolitics, the principles of justice, trustworthiness, and deliberation serve as the moral foundation for governance. Meanwhile, in the judiciary, honesty, accountability, andequality before the law are essential for realizing substantive justice. This study uses a qualitative descriptive approach through library research to analyze the relevance of Islamic values in these three institutional domains. The findings indicate that the successful integration of Islamic values depends on the alignment between state regulations and a substantive understanding of Islamic teachings, which emphasize humanity, inclusivity, and contextual adaptation to Indonesia's socio-cultural realities